Characterization of Si–Cu–C–Al quaternary interface of SiC/2A14 joint via counterintuitive laser butt welding. (July 2021) - Zhang, Mingyang; Wang, Chunming; Mi, Gaoyang; Jiang, Ping; Zhang, Xiong; Yan, Xiuhui
Abstract: SiCp /Al matrix composites (SiCp /AMCs) have be widely used in the aerospace structural components, space station solar cell structural framework. However, the double bottleneck of poor formability and low tensile strength exists in laser welding SiCp /AMCs. Here, the SiCp /2A14Al joints were prepared via counterintuitive laser butt welding. The Si–Cu–C–Al quaternary system nanometer precipitations were characterized. A new concept of 'Perforating Laser Welding' (PLW) was proposed, under which 205 MPa welded joint was successfully prepared. TEM results showed that amorphous Si was embedded in the Al matrix. AlCu was attached to Al4 C3 for heterogeneous nucleation-growth. Al4 C3 has a tightly bonded interface with Al matrix, which enhances the load transfer capability. This provides a two-level coupling window for SiCp /2xxx Al welded joint design: the 'Perforating Laser Welding' concept and the tailoring load transfer interface between AlCu/Al4 C3 and Al matrix. Highlights: A new concept of 'Perforating Laser Welding' (PLW) is proposed. Si–Cu–C–Al quaternary system nanometer precipitation phase was characterized. The strength of the 0.2 mm gap-joint is 49% higher than that of the 0 mm gap-joint.